2021
DOI: 10.1186/s12890-021-01458-x
|View full text |Cite
|
Sign up to set email alerts
|

Migration of ingested sharp foreign body into the bronchus: a case report and review of the literature

Abstract: Background Foreign body ingestion is a common emergence in gastroenterology. Foreign bodies are most likely to be embedded in the esophagus. The sharp ones may penetrate the esophageal wall and lead to serious complications. Case presentation A 72-year-old Chinese female was admitted to our hospital with a 4-day history of retrosternal pain and a growing cough after eating fish. Chest computed tomography scan indicated that a high-density foreign b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…This was similar to a study conducted by Hajiioannou et al, wherein there was an iatrogenic migration of an impacted pharyngeal foreign body of the hypopharynx to the pre-vertebral space [ 6 ]. Another study published by Qiu et al showed similar migration of ingested sharp foreign body into the bronchus [ 7 ].…”
Section: Discussionmentioning
confidence: 96%
“…This was similar to a study conducted by Hajiioannou et al, wherein there was an iatrogenic migration of an impacted pharyngeal foreign body of the hypopharynx to the pre-vertebral space [ 6 ]. Another study published by Qiu et al showed similar migration of ingested sharp foreign body into the bronchus [ 7 ].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the holmium laser is still of high security as a great amount of the energy can be absorbed by water and the penetration depth is no more than 0.5 mm, enabling the surrounding tissues to get mild injuries only. In a previous case, a fishbone punctured the bronchus through the esophagus and was removed successfully after being broken by holmium laser bronchoscopically ( 8 ). This demonstrates that it is feasible and effective to break the incarcerated foreign body with holmium laser and then remove it endoscopically.…”
Section: Discussionmentioning
confidence: 99%